2010
DOI: 10.1039/c0md00082e
|View full text |Cite
|
Sign up to set email alerts
|

PRIMACENES: novel non-cytotoxic primaquine-ferrocene conjugates with anti-Pneumocystis carinii activity

Abstract: Primacenes, novel ferrocene-primaquine conjugates, were synthesized and screened for their antimalarial and anti-pneumocystis activity. Primacenes obtained by coupling primaquine amino acid derivatives to ferrocenoic acid were significantly active against Pneumocystis carinii and devoid of cytotoxicity, thus being more selective than the parent drug.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
28
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 34 publications
(56 reference statements)
0
28
0
Order By: Relevance
“…Since several reports indicate that iron potentiates the leishmanicidal activity of several drugs (21,33), and since we have previously shown that ferrocene (Fc) derivatives of PQ are active against Plasmodium (19) and Pneumocystis (20), we next tested a series of Fc derivatives of PQ for activity against L. infantum promastigotes. The results obtained with compounds 5 to 10 ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since several reports indicate that iron potentiates the leishmanicidal activity of several drugs (21,33), and since we have previously shown that ferrocene (Fc) derivatives of PQ are active against Plasmodium (19) and Pneumocystis (20), we next tested a series of Fc derivatives of PQ for activity against L. infantum promastigotes. The results obtained with compounds 5 to 10 ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Other compounds of the PQ-Pro-Xaa series, i.e., 4a and c to i, were synthesized as previously described for compound 4b (38), and spectroscopic data as well as high-pressure liquid chromatography (HPLC) traces are available upon request. Synthetic procedures and chromatographic/spectroscopic data were reported elsewhere for compounds 5 to 10 (19,20), except for compound 7h, for which relevant procedures and data are available upon request.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This result agrees with our previous findings on PQ derivatives 4, as these organometallic compounds were also highly active against liver-stage parasites, regardless of whether a basic aliphatic amine group was present. Yet, compounds 4 which lacked a basic aliphatic amine group Scheme 1 Chemical structures of primaquine (1), its main metabolite, carboxyprimaquine (2), PQ derivatives formerly developed by us, namely, imidazoquines (3) 6,7 and primacenes (4), 8,9 and PRIMACINS herein reported (5): (i) PQ was coupled to cinnamic acids in the presence of 1.1 molar equivalents (eq.) of TBTU and 2 eq.…”
mentioning
confidence: 99%
“…5 To this end, we have successfully developed imidazoquines (3 in Scheme 1) 6,7 and primacenes (4 in Scheme 1), 8,9 peptidomimetic and organometallic derivatives of PQ with promising antimalarial properties, respectively. Now, we disclose a new family of PQ derivatives, the PRIMACINS (5 in Scheme 1), obtained by coupling PQ to cinnamic acids, as the latter was formerly reported to possess interesting antimalarial properties.…”
mentioning
confidence: 99%